Perfiles del profesorado a partir del conocimiento de los recursos tecnológicos y su relación con el uso que hacen de estas tecnologías - Suárez, Jesús M.; Almerich, Gonzalo; Belloch, Consuelo; Orellana, Natividad (Revista Complutense de Educación, 2010)
This paper analyzes the relationship of technological competence with ICT use by teachers, both personal-professional use and with students in the classroom. Both are essential dimensions in order that teachers get the confidence to integrate ICT. Through a survey design, the opinion of primary and secondary teachers in the Valenciana Community has picked up (n = 868). The questionnaire is the method of collecting information. The results indicate the existence of four different profiles of teachers depending on level of technological competence, which are strongly related to the ICT use, particularly with personal-professional use. The level of competence involves the use of greater variety of technological resources.
Keywords: Information and communication technologies; Teacher; Technological competences; Personal-professional use; Use in the classroom; Primary education; Secondary education